2016
DOI: 10.1186/s40246-016-0092-0
|View full text |Cite
|
Sign up to set email alerts
|

A genomic case study of desmoplastic small round cell tumor: comprehensive analysis reveals insights into potential therapeutic targets and development of a monitoring tool for a rare and aggressive disease

Abstract: BackgroundGenome-wide profiling of rare tumors is crucial for improvement of diagnosis, treatment, and, consequently, achieving better outcomes. Desmoplastic small round cell tumor (DSRCT) is a rare type of sarcoma arising from mesenchymal cells of abdominal peritoneum that usually develops in male adolescents and young adults. A specific translocation, t(11;22)(p13;q12), resulting in EWS and WT1 gene fusion is the only recurrent molecular hallmark and no other genetic factor has been associated to this aggres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 35 publications
2
33
0
Order By: Relevance
“…Inactivating mutations in STAG2 are the most frequent accompanying somatic mutation in Ewing sarcoma, occurring in approximately 17% of cases, and are associated with poor outcome (10,51). To the best of our knowledge, among the relatively few cases of DSRCT that have either undergone extensive genetic sequencing (13,16,46) or sequencing focused specifically on accompanying STAG2 or TP53 mutations (45), only one additional case with a STAG2 mutation has been reported (45). This patient's EWSR1-WT1 gene fusion and accompanying inactivating STAG2 splice site mutation were detected within tumor tissue and within plasma derived cell free DNA (45).…”
Section: Discussionmentioning
confidence: 99%
“…Inactivating mutations in STAG2 are the most frequent accompanying somatic mutation in Ewing sarcoma, occurring in approximately 17% of cases, and are associated with poor outcome (10,51). To the best of our knowledge, among the relatively few cases of DSRCT that have either undergone extensive genetic sequencing (13,16,46) or sequencing focused specifically on accompanying STAG2 or TP53 mutations (45), only one additional case with a STAG2 mutation has been reported (45). This patient's EWSR1-WT1 gene fusion and accompanying inactivating STAG2 splice site mutation were detected within tumor tissue and within plasma derived cell free DNA (45).…”
Section: Discussionmentioning
confidence: 99%
“…The typical histopathological appearance of DSRCTs includes large necrotic area, sharply demarcated nests of different sizes containing small round cells with hyperchromatic nuclei and scanty faint eosinophilic cytoplasm, or spindle cells embedded in a desmoplastic stroma. These cells mostly exhibit epithelial, mesenchymal, and neural markers like cytokeratin, desmin, and smooth muscle actin (SMA) [14]. Desmoplastic smallround-cell tumor arises from mesenchymal cells of the abdominopelvic peritoneum.…”
Section: Discussionmentioning
confidence: 99%
“…The authors subsequently classified the affected genes by biological function and more than a quarter of the mutated genes belonged to either DNA damage-response network (DDR) or genes that belong to mesenchymal-epithelial reverse transition (MErT), and EMT (epithelial-mesenchymal transition). Of interest, another WES study in DSRCT in one patient with DSRCT showed 12 somatic and 14 germline events in genes which were predominantly involved in mesenchymal differentiation (24) Poly(ADP-ribose) polymerase or PARP inhibitor has been suggested to be active in tumors with deficiency in DDR and in combination with DNA damaging agents (25). Currently there is a clinical trial underway for refractory pediatric solid tumors, which is investigating PARP inhibition using olaparib (26).…”
Section: Molecular Characteristics Of Dsrctmentioning
confidence: 99%